ANTARA HARAPAN DAN REALITA: IMPLEMENTASI KEBIJAKAN ORGANISASI PERANGKAT DAERAH - Zulpikar Haris Faozan (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
This study intends to describe the policy performance of the Government Regulation Number 41 Year 2007 on Local Government Agencies through five indicators: effectiveness, efficiency, sufficiency, accuracy, and responsiveness.This is a descriptive case study conducted in the District of Konawe and the Muncipality of Kendari. Primary data are collected through open and closed questions, whereas the secondary ones are collected from some relevant documents. Every head of Local Government Agencies in each locus becomes the respondents of this research. Data are analyzed by triangulation method, and the results are measured by the achievement level of policy implementation based on five indicators above. After that, all results are categorized into three levels: Low Level (ranging from 0 to 1.00), Modest Level (ranging from 1.01 to 2.00),and High Level (ranging from 2.01 to 3.00). This study shows that the achievement level of policy performance in the District of Konawe and Muncipality of Kendari lies at the Modest Level. Furthermore, the study reveals some critical issues in the implementation of the policy: need for surveillanceprogram from central government, political interests, administrative constraints, lack of resources (financial, apparatus, infrastructure), and cultural constrictions. To solve the problems, collaboration among central, provincial and local governments becomes a necessity in aligning the policy.